2014
DOI: 10.1177/0886260514555013
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of an HIV/STI Risk-Reduction Program for Incarcerated Women Who Have Experienced Interpersonal Violence

Abstract: HIV and other sexually transmitted infections (STIs) and interpersonal violence (IV; e.g., childhood abuse, partner violence, and rape) victimization are significant and interconnected public health problems facing incarcerated women. We adapted a best-evidence HIV prevention intervention for women (the Women's CoOp) to address sexual safety among incarcerated women with histories of interpersonal violence victimization. The standard Women's CoOp teaches safe sex, substance use harm reduction, and violence pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 70 publications
0
26
0
1
Order By: Relevance
“…We integrated content on common coping responses to trauma and ways of managing these responses in relation to sex risk that was used in a previous adaptation of the WHC that focused on trauma among women incarcerated in US prisons. 28 We also added new cognitive-behavioral therapy (CBT) material on identifying and managing emotional and other triggers for substance use through mindfulness practice, thought stopping techniques, and other emotional regulation and coping strategies. We included these new components as they have been shown to reduce trauma-related internal triggers for substance use.…”
Section: Resultsmentioning
confidence: 99%
“…We integrated content on common coping responses to trauma and ways of managing these responses in relation to sex risk that was used in a previous adaptation of the WHC that focused on trauma among women incarcerated in US prisons. 28 We also added new cognitive-behavioral therapy (CBT) material on identifying and managing emotional and other triggers for substance use through mindfulness practice, thought stopping techniques, and other emotional regulation and coping strategies. We included these new components as they have been shown to reduce trauma-related internal triggers for substance use.…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence of mental health issues in general among incarcerated women has been well-documented (e.g., Gunter et al, 2012; Peters et al, 1997), as well as the prevalence of co-occurring mental health and substance abuse issues (Sacks, 2004; Staton-Tindall, Leukefeld, & Webster, 2003). Histories of victimization and violence among incarcerated women are also well-documented (e.g., Johnson et al, 2015; Radatz & Wright, 2015; Saxena, Messina, & Grella, 2014), and victimization has been noted as a factor distinguishing first time and repeat women offenders (Herbst, et al, 2016). Thus, these findings are fairly consistent with the broader literature for female offenders.…”
Section: Discussionmentioning
confidence: 99%
“…Of the eight studies that were included in the integrative review, five were identified in MEDLINE ( 25 - 29 ) , one in Cochrane ( 30 ) , one in ScienceDirect ( 31 ) , and one in CINAHL ( 32 ) . Most of the studies were developed in the United States (7) ( 25 - 30 , 32 ) and all of them were written in English. Only one article was prepared in Brazil ( 31 ) .…”
Section: Resultsmentioning
confidence: 99%